2022
DOI: 10.1039/d2se01007k
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of PET waste electroreforming with green hydrogen generation using bifunctional catalyst

Abstract: Cost-effective and high-efficiency bifunctional electrocatalysts for electrooxidation of polyethylene terephthalate (PET) waste and green hydrogen generation are very crucial for practical implementation yet rarely reported. Herein, a bifunctional catalyst of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…11), the intersection of the semicircular arc and the real axis represents the solution resistance ( R s ), and the diameter of the semicircular arc represents the electrochemical reaction resistance ( R ). 3,48–51 The insets are a histogram of the R s and R values and fitted circuit diagram, where it can be seen that the R s of Co/NF-CoC 2 O 4 (0.95672 Ω) is higher than that of Co/NF (0.91455 Ω) and Co/NF-CoC 2 O 4 -Co (0.82989 Ω). The electrical conductivity of Co is better than that of CoC 2 O 4 , and Co can provide a fast transfer channel for electrons, and thus Co/NF-CoC 2 O 4 -Co had a lower R s relative to Co/NF and Co/NF-CoC 2 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…11), the intersection of the semicircular arc and the real axis represents the solution resistance ( R s ), and the diameter of the semicircular arc represents the electrochemical reaction resistance ( R ). 3,48–51 The insets are a histogram of the R s and R values and fitted circuit diagram, where it can be seen that the R s of Co/NF-CoC 2 O 4 (0.95672 Ω) is higher than that of Co/NF (0.91455 Ω) and Co/NF-CoC 2 O 4 -Co (0.82989 Ω). The electrical conductivity of Co is better than that of CoC 2 O 4 , and Co can provide a fast transfer channel for electrons, and thus Co/NF-CoC 2 O 4 -Co had a lower R s relative to Co/NF and Co/NF-CoC 2 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, researchers have tried to transform EG into other value-added products like formate via electrochemical oxidation under alkaline conditions. 30–34…”
Section: Introductionmentioning
confidence: 99%
“…Hence, researchers have tried to transform EG into other value-added products like formate via electrochemical oxidation under alkaline conditions. [30][31][32][33][34] In this work, we combined the anodic oxidation process of EG, derived from hydrolyzing PET plastic waste, using CuCo@rGO electrocatalyst, with the cathodic CO 2 reduction reaction (CO 2 RR) using a bismuth carbonate (Bi 2 O 2 CO 3 )-functionalized reduced graphene oxide (BOC@rGO) electrocatalyst. BOC@rGO was prepared from bismuth phosphate@reduced graphene oxide (BiPO 4 @rGO) synthesized using a straightforward one-step hydrothermal method, followed by electrochemical activation.…”
Section: Introductionmentioning
confidence: 99%
“…Half-cell reactions on the anode and cathode suggest that the overall reaction in MeOH electrolysis is the dehydrogenation of MeOH (eqn (5)), whereby value-added products (FA and H 2 ) are formed on both the anode and cathode simultaneously. H 2 generation integrated with the oxidation of organic molecules has been paid attention, 56–61 and simultaneous synthesis of formate and H 2 from methanol was recently reported. 62,63 This study revealed that the Pd catalyst is effective for the synthesis of H 2 and FA from methanol electrolysis.CH 3 OH → HCHO + H 2 …”
Section: Resultsmentioning
confidence: 99%